An assessment of the maritime archaeological potential of the Eastern Coast Line of Table Bay, between the old Salt River Mouth and Blouberg - Mavrodinov, Nikolay Stefanov (Department of Archaeology, 2026)
" ... maritime archaeology is a scientific approach which attempts to study people's past relations to the sea through surviving material evidence and all available additional evidence of whatever nature" (Werz 1997;20}. In the context of the above definition, this project falls wi thin the domain of the research specialisation or subdiscipline of maritime archaeology. It is centred around researching maritime archaeological sites and creating a data base of such sites and their terrestrial counterparts for a particular coastal area, namely the stretch between the old Salt River mouth and Blouberg on the eastern side of Table Bay, South Africa. It is also part of a larger project, the Maritime Archaeological Proj ect of Table Bay or MAP, which deals with the maritime archaeological potential of this area. The objectives of MAP are as follows: